The effect of imidazolium-based ionic liquids on the tensile properties of gellan gum/KCF biocomposite films - a prelude study - Shamsuri, Ahmad Adlie; Abdan, Khalina; Kaneko, Tatsuo (Sciencedomain International, 2021)
In this prelude study, the gellan gum/kenaf core fiber (KCF) biocomposite films were fabricated with the addition of imidazolium-based ionic liquids such as 1-butyl-3-methylimidazolium chloride (Bmim Cl), 1,3-dimethylimidazolium methylsulphate (Dmim MeSO4), 1-ethyl-3-methylimidazolium acetate (Emim Ac), and 1-ethyl-3-methylimidazolium trifluoromethanesulfonate (Emim OTf). The fabrication of the biocomposite films was carried out by mixing KCF and the ionic liquids in an aqueous solution, followed by dissolution of gellan gum in the same solution at a temperature of 90°C. The mixed solution was gelled at room temperature, and the formed gel was dried in an oven at 40°C for 48 hours to obtain a freestanding biocomposite film. The fabricated films were characterized by using a universal testing machine to acquire tensile properties. The tensile test results indicated that the biocomposite film added with Emim Ac possesses a higher tensile extension at maximum (up to 24%) than the biocomposite film without ionic liquid (added with glycerol). In addition, the biocomposite film added with Emim OTf has a higher tensile modulus at maximum (up to 758%) compared to the biocomposite film without ionic liquid. In conclusion, the tensile properties of the gellan gum/KCF biocomposite films can be improved with the addition of Emim-based ionic liquids with different counter anions.